Chinese Modern Cartoon. A transcultural approach to Modern Sketch (Altre Modernità, 2018)
Since the second half of the XIX century, Chinese print media have been involved in intercultural exchanges that permanently modified the editorial production in Shanghai, the Chinese capital of modern press. The evolution of the visual language of cartoon (single-panelled, mainly satirical vignette) has to be located in this context, i.e. in a liminal space characterized by the contact and the intermingling of semiotic systems as well as genres and interests. On one hand, the cartoon format is by itself a hybrid genre, born as a complex iconic-verbal construction. On the other hand, Chinese modern cartoon, which emerged and developed at the turn of the XX century along with the evolution of journalism and entertainment in semi-colonial Treaty Ports, reflects and participates into the process of bridging cultural boundaries through adaptive and integrative communication strategies (métissage). The present essay will firstly examine the asymmetrical cultural exchanges between European-American (Punch-and-Puck format) and Chinese culture, and inside the Sino-Japanese 'interliterary community' of the late XIX century. Besides synthetizing the state of the art, the paper will also elaborate on the possibility of a Punch/Puck legacy in 1920s-1930s China. Secondly, through the analysis of selected exempla from the cartoon magazine Modern Sketch (Shidai Manhua, 1934-1937), I will present significant aspects of the transcultural processes occurred in China during the golden years of cartooning.